Food fraud vulnerability assessment: Towards a global consensus on procedures to manage and mitigate food fraud. (June 2020) - Barrere, Virginie; Everstine, Karen; Théolier, Jérémie; Godefroy, Samuel
Abstract: Background: Food fraud represents a risk to the food industry and food business operators are required to conduct a food fraud vulnerability assessment to be in compliance with GFSI requirements. There is currently no globally-recognized standardized process for food fraud mitigation and some food business operators have found meeting the requirements to be challenging. Scope and approach: This work summarizes the main aspects of publicly-available food fraud vulnerability assessment (FFVA) tools and resources, describes the general FFVA process based on a consensus of the previous work, and highlights gaps in this process that should be addressed. Key findings and conclusions: The main gaps identified were: appropriately grouping and prioritizing products/ingredients, evaluating the vulnerability of multi-component finished products, collecting and evaluating supporting data, evaluating potential public health and economic impacts, resource constraints among small/medium-sized companies and in developing countries, understanding and creating standards for analytical detection methods for fraud, and evaluating fraud vulnerability in food packaging. This work can support discussions at a global level that may eventually lead to a consensus process for a FFVA, for example, those conducted under the auspices of the Codex Alimentarius Commission. Highlights: Food fraud related risks have to be assessed by food industries. No standard for fraud management and mitigation has been internationally recognized. Guidelines for food fraud management exist and are implemented in food industries. A consensus should be developed and adopted by international organizations. Gaps stemming from existing guidelines have been identified and addressed.